Distribution behavior of inclusions in compact-strip-produced martensitic steel and its influence on mechanical properties. (10th April 2023) - Wang, Jing; Xue, Peng; Zhang, Laiqi; You, Li; Zhu, Xiaodong; Wang, Shuize; Zhong, Yong; Mao, Xinping
Highlights: Distribution behavior of inclusions in CSP-produced martensitic steel was studied. High inclusion density resulted in lower total elongation and impact toughness. MnS inclusion with high aspect ratio led to stronger mechanical anisotropy. Effect mechanism of inclusions features on the microcracks initiation was studied. Abstract: The distribution behavior of inclusions in martensitic steel produced by compact strip production process (CSP-MS) and its influence on mechanical properties were systematically investigated. The inclusions in the CSP-MS specimen are mainly composed of spherical Al2 O3 −CaO−CaS, MnS with high aspect ratio and small-sized TiN, whereas many coarse cuboidal TiN inclusions do exist in conventional martensitic steel (Con-MS). The high inclusion density of the CSP-MS specimen resulted in lower total elongation and impact toughness, and the MnS inclusions with high aspect ratio led to significantly stronger mechanical anisotropy than that for Con-MS specimen. The in-situ tensile results indicated that when the fracture direction is parallel to MnS direction, the microcracks induced by MnS inclusions tend to propagate into the matrix, leading to the formation of valley-like features, which significantly deteriorate the properties such as the total elongation and impact toughness. The microcracks caused by TiN inclusions are sharper than those caused by spherical Al2 O3 −CaO−CaS inclusions, and are easy to propagate into the matrix. This work is expected to guide the optimization of the mechanical properties of martensitic steels produced by CSP process and provide a theoretical basis for the CSP process design.